Grammaticalization of future-time reference markers in Korean and Thai: a focus on morphosyntax and conceptual motivation - Seongha Rhee; Kultida Khammee (Penerbit Universiti Kebangsaan Malaysia, 2024)
Contemporary Korean and Thai both have a number of forms that denote the future-time reference. The grammatical statuses of these forms are widely variable in terms of their morphosyntax, and thus, there exists some debate about whether some of them can be regarded as future tense markers. By virtue of the dynamic, panchronic nature of grammaticalization theory, there is an advantage in viewing the change, both holistically and microscopically, from the historical source lexeme, if available, to the grammatical forms and functions in the contemporary states of the languages. An investigation into the grammaticalization patterns of the broadly defined future-time references in the two languages reveals a number of interesting features. Future-time references in the two languages developed from very different lexical sources, e.g., TEMPORAL POSTERIORITY and MODE in Korean as compared with KNOWLEDGE and TEMPORAL PROXIMITY, as well as contextually inferred IMMINENT REALIZATION in Thai. The two languages also exhibit idiosyncrasies reflecting typological features, e.g., argument omissibility and agglutination in Korean and strong pragmatic orientation, verb serialization, and preference for polylexemic units in lexicalization and grammaticalization in Thai. Despite the differences in conceptual sources and developmental paths, Korean and Thai show commonalities in the modal functions of the future-time reference markers, which lends support to the thesis that these modal notions are strongly connected to the notion of futurity across languages. Also notable is that in Thai, reinforcement is often observed, supposedly for boosting perceptual salience and conceptual strengthening in grammaticalization.